Utilization of Bendrat Wire fiber on the Mechanical Properties of Geopolymer Concrete - Sucahyo, Septian Gusti; Nurtanto, Dwi; Utami, Nanin Meyfa (BERKALA SAINSTEK, 2023)
One of the problems in the construction field, especially concrete, is to reduce cracking due to the brittle nature of the concrete itself and increase the strength of the concrete. One of the ingredients to minimize cracks in concrete is the addition of fiber in the concrete mixture. Therefore, additional innovation is needed in the manufacture of concrete. So, this research was carried out by discussing the use of bendrat wire on the mechanical properties of geopolymer concrete. This study aims to determine the results of compressive strength, split tensile strength, and flexural strength with variations in the addition of 0%, 6%, 12%, and 18% were using a 2% superplasticizer with a concrete age of 28 days. The addition of bendrat wire from 0%, 6%, 12%, and 18% of the test results has increased. For compressive strength, respectively, 40.34 MP, 40.552 Mpa, 40.977 Mpa, and 41.189 MPa. For the splitting tensile strength result, which is 2.07 MPa;, 2.123 MPa, 2.176 MPa, and 2.229 MPa. For flexural strength, 4.05 Mpa, 4.09 Mpa, 4.16 Mpa, and 4.25 MPa.